Reflection to enhance dental students´ awareness of and comfort with uncertainty – an experimental study - Joséphine Brodén; Helena Fransson; Niklas Vareman; Maria Pigg (BMC Medical Education)
Abstract Background Uncertainty is present in many situations in dental practice, but must not prevent wise clinical decision-making. Dental education should acknowledge uncertainty and teach useful management strategies. This study explored if dental students are aware of, and comfortable with uncertainty. The aims were to (i) measure students’ comfort or discomfort with and awareness of uncertainty while conducting risk assessment, and (ii) investigate whether a reflection exercise makes the students more aware of, and comfortable with, uncertainty. Methods In January 2021, final-year students (n = 51) were randomized to either a structured written reflection exercise (intervention) or to a control exercise. Five months later, in June, each group was assigned the other exercise (cross-over design; ensuring a sufficient sample). Students’ statements of uncertainty and comfort were gathered using a developed questionnaire before and after the exercises. The students were blinded to which of the exercises was the intervention. The exercises and questionnaire were administered in mandatory sessions on an internet-based learning platform, ensuring anonymity and informed consent. Potential carryover effects were mitigated by analyzing intervention exercise data from both groups but control exercise data only from the first group. Results At baseline 80% (41/51) of the students stated feeling very uncertain, uncertain or neither certain nor uncertain about assessing the risk and 84% were comfortable or very comfortable with their ability to handle the situation, with no between-group differences. The majority, 57% (29/51) of the students stated that they thought an experienced colleague would feel certain or very certain. After the exercise in June, 36% (9/25) of the students exposed to the reflection exercise changed their statements on how certain they felt about their capacity to handle the case. Conclusions The exercise did not affect the awareness of uncertainty and the students’ comfort with it, as the majority of students stated already feeling comfortable in their ability to handle the situation at baseline. However, the reflection exercise highlighted the students’ perception that experience is important in managing uncertainty. There is a need for further research to better understand students’ and teachers’ perception and attitudes to uncertainty and its effective management. Clinical trial number Not applicable.